2014
DOI: 10.4012/dmj.2012-015-r
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro osteoinduction of human mesenchymal stem cells in biomimetic surface modified titanium alloy implants

Abstract: Interaction between cells and implant surface is crucial for clinical success. This interaction and the associated surface treatment are essential for achieving a fast osseointegration process. Several studies of different topographical or chemical surface modifications have been proposed previously in literature. The Biomimetic Advanced Surface (BAS) topography is a combination of a shot blasting and anodizing procedure. Macroroughness, microporosity of titanium oxide and Calcium/Phosphate ion deposition is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It has been previously demonstrated that in vivo porous titanium implants have different biological behaviors: increased porosity and pore size showed a direct positive effect on the amount of new bone growth . Biomimetic modified titanium surfaces were important to improve cell adhesion, proliferation and osteogenic differentiation in the absence of any differentiation molecule . In vitro experiments demonstrated that a combination of surface properties like microstructure and high energy increased osteoblast maturation of MSCs or progenitor cells via autocrine and paracrine regulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that in vivo porous titanium implants have different biological behaviors: increased porosity and pore size showed a direct positive effect on the amount of new bone growth . Biomimetic modified titanium surfaces were important to improve cell adhesion, proliferation and osteogenic differentiation in the absence of any differentiation molecule . In vitro experiments demonstrated that a combination of surface properties like microstructure and high energy increased osteoblast maturation of MSCs or progenitor cells via autocrine and paracrine regulation .…”
Section: Discussionmentioning
confidence: 99%
“…43 Biomimetic modified titanium surfaces were important to improve cell adhesion, proliferation and osteogenic differentiation in the absence of any differentiation molecule. 44 In vitro experiments demonstrated that a combination of surface properties like microstructure and high energy increased osteoblast maturation of MSCs or progenitor cells via autocrine and paracrine regulation. 45 The trabecular structure of the scaffold here used is the main factor of the osteogenic differentiation of hASCs in "in vitro" conditions: the addition of osteogenic factors does not improve both gene and protein expression of markers of differentiation of stem cells toward osteoblastic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Previous studies to enhance the surface of Ti as an implant material were challenged by confounding factors. 4 These included physical characteristics (e.g., surface roughness) and multiple biologically active factors in the serum when the samples were tested in vitro . 4 , 6 …”
Section: Introductionmentioning
confidence: 99%
“… 4 These included physical characteristics (e.g., surface roughness) and multiple biologically active factors in the serum when the samples were tested in vitro . 4 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation